2019
DOI: 10.1093/advances/nmz043
|View full text |Cite
|
Sign up to set email alerts
|

Almond Consumption and Risk Factors for Cardiovascular Disease: A Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Evidence suggests that eating nuts may reduce the risk of cardiovascular disease (CVD). We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) evaluating almond consumption and risk factors for CVD. MEDLINE, Cochrane Central, Commonwealth Agricultural Bureau, and previous systematic reviews were searched from 1990 through June 2017 for RCTs of ≥3 wk duration that evaluated almond compared with no almond consumption in adults who were either healthy or at risk for CVD. The mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 37 publications
3
71
3
Order By: Relevance
“…These findings are somewhat in line with previous findings, with systematic reviews of randomised controlled trials with various nuts having reported improvements in MetS criteria [51]. Systematic reviews focused on almonds [52,53] or a range of tree nuts and peanuts have also found improvements in lipids [54] and insulin resistance (HOMA-IR) [55] and some studies have reported improvements in inflammatory biomarkers [56]. Furthermore, there was a significant reduction in systolic blood pressure in the AED group compared with the NFD group.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are somewhat in line with previous findings, with systematic reviews of randomised controlled trials with various nuts having reported improvements in MetS criteria [51]. Systematic reviews focused on almonds [52,53] or a range of tree nuts and peanuts have also found improvements in lipids [54] and insulin resistance (HOMA-IR) [55] and some studies have reported improvements in inflammatory biomarkers [56]. Furthermore, there was a significant reduction in systolic blood pressure in the AED group compared with the NFD group.…”
Section: Discussionsupporting
confidence: 92%
“…A previous review [5] reported no effect of nut consumption on body weight from 4 meta-analyses of prospective and intervention studies [42][43][44][45]. In this review, we included 3 more meta-analyses of observational and interventional studies [5][6][7]. As a result, nut consumption still did not significantly affect body weight based on 7 meta-analyses [5][6][7][42][43][44][45].…”
Section: Body Weightmentioning
confidence: 94%
“…Reference lists of chosen articles were also screened for related publications. A previous review [4] examined 34 meta-analyses, and this review added 7 new meta-analyses [5][6][7][8][9][10][11]. A flow chart for the identified studies is included in this review in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations